Pengaruh Lingkungan Kerja Dan Kompentensi Terhadap Kepuasan Kerja Dengan Pengalaman Kerja Karyawan Sebagai Variabel Intervening Pada Puskesmas Lubuk Kilangan - Julizar Nasrul; Jhon Veri; Nila Pratiwi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to examine the Effect of Work Environment and Competence on Job Satisfaction with Work Experience as an Intervening Variable using secondary data obtained by distributing questionnaires to 47 permanent employees who are used as respondents at the Lubuk Kilangan Health Center. In this study using the analysis tool Structural Equation Modeling (SEM) using Partial Least Square (PLS). The results of this study indicate that (1) the work environment has a positive and significant effect (0.015 <0.05) on work experience. (2) Competence has a positive and significant effect (0.00 <0.05) on work experience. (3) Work Environment has no significant effect (0.056 > 0.05) on Job Satisfaction. (4) Competence has a positive and significant effect (0.000 <0.05) on job satisfaction. (5) Work Experience has a positive and significant effect (0.000 <0.05) on Job Satisfaction. (6) Work environment has a positive and significant effect (0.011 <0.05) on job satisfaction through work experience. (7) Competence has a positive and significant effect (0.000 <0.05) on job satisfaction through work experience. (8) The contribution of work environment and competency variables to job satisfaction is 0.981 or 98.1% and the remaining 1.9% is influenced by other variables not examined in this study. (9) The contribution of work environment variables, competence and work experience to job satisfaction is 0.900 or 90.0% and the remaining 1% is influenced by other variables not examined by this study.